THE ROLE AND IMPORTANCE OF COMMUNICATIVE COMPETENCE IN TECHNICAL EDUCATION (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the essence, significance, and effective methods of developing communicative competence among students of technical higher education institutions. It highlights the importance of improving students’ ability to communicate professionally in foreign languages (particularly English), which plays a key role in increasing their competitiveness in the global labor market.